Consideration of Temperature Factors when Designing Butterfly Check Valves for Hazardous Production Facilities - Julia Soboleva; Abdulmejid Kerimov; Abas Lampezhev (Civil Engineering Journal, 2023)
The safety of hazardous production facilities is directly related to the reliability of pipeline systems, which must be ensured regardless of environmental conditions. Accidents on pipeline sections can have catastrophic consequences associated with damage to human health and the environment. Damage to the metal of pipeline elements during operation due to internal corrosion occurring under the influence of the working fluid is one of the main reasons for failure. This study aims to develop an improved butterfly check valve (BCV), which is a pipeline element. For this purpose, various structural materials used in the production of check valves were analyzed, and the changes in their mechanical properties under the influence of temperature were also considered. Based on this material, a butterfly check valve was developed. The stress-strain state of the developed structure was assessed using the finite element method (FEM). Strains, stresses, and displacements were calculated to evaluate valve performance. These calculations are necessary to determine the most loaded elements of the BCV at the maximum and minimum ambient temperatures. The following conclusions were obtained: X6CrNiTi18-10 stainless steel grade is the most suitable material for piping systems transporting liquids in production facilities. On the basis of the simulation results, the values of equivalent stresses, maximum strains, and displacements were obtained. The research results confirmed the performance of the improved design, the unhindered motion of the working fluid in the working direction, and the convenient connection to horizontal and vertical sections of the pipeline. Doi: 10.28991/CEJ-SP2023-09-020 Full Text: PDF